ANALYSIS THE USE OF PLURAL NOUNS IN “SELECT READINGS’ BY LINDA LEE AND ERIK GUNDERSEN - Aulia Putri Senjani (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
This research aims to search into one of the most commonly found forms of a plural noun in the book "Select readings" by Linda Lee and Erik Gundersen. During this article, the author focuses on plural nouns. The author uses qualitative descriptive techniques in locating knowledge. Rodney (2005: 83) defines that noun may be a grammatically distinct class of words that incorporates those denoting all types of object, like persons, animals, and inanimate objects. According to (Frank 1972:13), nouns in inflections are nouns with particular plural ending, like -s/-es/-is. The plural noun encompasses an operation of the noun as having over one person/animal/object/idea. In writing, this study will build textbook readers "Select Readings" in designate the plural noun. Then choose "Select Readings" by Linda Lee and Erik Gundersen for EFL as preparation material for such tests as TOEFL, IELTS, etc. The“Select Readings” contains reading and exercise texts..